Effects of High Fat Versus Normal Diet on Extracellular Vesicle–Induced Angiogenesis in a Swine Model of Chronic Myocardial Ischemia - Aboulgheit, Ahmed (J Am Heart Assoc, 2021)
BACKGROUND: Mesenchymal stem cell–derived extracellular vesicles (EVs) promote angiogenesis in the ischemic myocardium. This study examines the difference in vascular density, myocardial perfusion, molecular signaling, and gene expression between normal diet (ND) and high fat diet (HFD) groups at baseline and following intramyocardial injection of EVs. METHODS AND RESULTS: Intact male Yorkshire swine fed either an ND (n=17) or HFD (n=14) underwent placement of an ameroid constrictor on the left circumflex coronary artery. Subsequently, animals received either intramyocardial injection of vehicle‐saline as controls; (ND‐controls n=7, HFD‐controls, n=6) or EVs; (ND‐EVs n=10, HFD‐EVs n=8) into the ischemic territory. Five weeks later, myocardial function, perfusion, vascular density, cell signaling, and gene expression were examined. EVs improved indices of myocardial contractile function, myocardial perfusion, and arteriogenesis in both dietary cohorts. Interestingly, quantification of alpha smooth muscle actin demonstrated higher basal arteriolar density in HFD swine compared with their ND counterparts; whereas EVs were associated with increased CD31‐labeled endothelial cell density only in the ND tissue, which approached significance. Levels of total endothelial nitric oxide synthase, FOXO1 (forkhead box protein O1) , transforming growth factor‐β, phosphorylated VEGFR2 (vascular endothelial growth factor receptor 2), and phosphorylated MAPK ERK1/ERK2 (mitogen‐activated protein kinase) were higher in ischemic myocardial lysates from ND‐controls compared with HFD‐controls. Conversely, HFD‐control tissue showed increased expression of phosphorylated endothelial nitric oxide synthase, phosphorylated FOXO1, VEGFR2, and MAPK ERK1/ERK2 with respect to ND‐controls. Preliminary gene expression studies indicate differential modulation of transcriptional activity by EVs between the 2 dietary cohorts. CONCLUSIONS: HFD produces a profound metabolic disorder that dysregulates the molecular mechanisms of collateral vessel formation in the ischemic myocardium, which may hinder the therapeutic angiogenic effects of EVs.